Knowledge, Attitude and Behavior of Dietary Salt Intake among Staff at a Public University in Selangor - Ab Hamid, Mohd Ramadan; Mat Jani, Azni Afifah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study examines knowledge, attitude and behavior related to dietary salt intake among UiTM Puncak Alam staff. A cross-sectional study was conducted among 300 UiTM Puncak Alam staff. Respondents were recruited conveniently to complete a self-administered questionnaire that provides information on knowledge, attitude and behavior related to dietary salt. Descriptive statistics were used to report the survey findings. Results showed that most of the respondents (95.7%) had a knowledge that overeating salt could damage their health. However, only 35.7% of the respondents recognized the daily recommendation of salt intake and 40.0% of them were able to identify the difference between salt and sodium. Regarding attitude, only 28.3% of respondents believed their salt intake would exceed dietary guidelines. In practice, 31.4% of respondents controlled their salt intake by avoiding consuming processed food, and 18.0% referred to salt labels on food packages. This study showed that UiTM Puncak Alam staff was knowledgeable on particular aspects of salt. However, their attitudes are less favorable, and they need to improve their practices toward dietary salt intake to achieve target salt intake.